2021
DOI: 10.1029/2020gl092121
|View full text |Cite
|
Sign up to set email alerts
|

Turning the Orogenic Switch: Slab‐Reversal in the Eastern Alps Recorded by Low‐Temperature Thermochronology

Abstract: Seismic tomography results from the eastern European Alps have led to the hypothesis that a change in subduction polarity also occurred there (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 151 publications
(245 reference statements)
5
37
0
Order By: Relevance
“…Previous thermo‐kinematic modeling studies in fold‐and‐thrust belts elsewhere (e.g., Lock & Willett, 2008; McQuarrie et al., 2019; McQuarrie & Ehlers, 2017) showed that exhumation associated with rock motion along mid‐crustal ramps produces a characteristic U‐shaped pattern of predicted thermochronological ages. Such thermochronometric age patterns have been observed in numerous fold‐and‐thrust belts around the world (e.g., Alps, Eizenhöfer et al., 2021; Hindukush, Kufner et al., 2016; Southern Alps, New Zealand, Batt et al., 2000), including the Southern Patagonian Andes (Fosdick et al., 2013).…”
Section: Discussionmentioning
confidence: 87%
“…Previous thermo‐kinematic modeling studies in fold‐and‐thrust belts elsewhere (e.g., Lock & Willett, 2008; McQuarrie et al., 2019; McQuarrie & Ehlers, 2017) showed that exhumation associated with rock motion along mid‐crustal ramps produces a characteristic U‐shaped pattern of predicted thermochronological ages. Such thermochronometric age patterns have been observed in numerous fold‐and‐thrust belts around the world (e.g., Alps, Eizenhöfer et al., 2021; Hindukush, Kufner et al., 2016; Southern Alps, New Zealand, Batt et al., 2000), including the Southern Patagonian Andes (Fosdick et al., 2013).…”
Section: Discussionmentioning
confidence: 87%
“…1), recent geophysical data suggest that the subducted European slab is detached from the orogenic crust and dips steeply to the NNE (Handy et al 2021;Paffrath et al 2021). A recent switch in subduction polarity with a northward subduction of the Adriatic plate may have occurred here in the Miocene (Kästle et al 2020;Eizenhöfer et al 2021).…”
Section: Geological Settingmentioning
confidence: 85%
“…Large thrust fault systems dipping in opposite (pro‐ and retro‐)directions (e.g., Contact Fault and Border Ranges Fault in the Yakutat collision zone of southeast Alaska; Arkle et al, 2013) are characteristic features of many continental orogens described as “doubly vergent” (Argand, 1916; Eizenhöfer et al, 2021; Willett et al, 1993). Our results show that a higher viscosity of the interface layer (i.e., a stronger mechanical connection between the subducting and overriding plate) favours deformation accommodation along trench‐parallel lithospheric‐scale shear bands and, therefore, reduces the influence of the curved geometry of the subducting plate (i.e., the central indenter bulge) on the overall rock uplift patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Large thrust fault systems dipping in opposite (pro-and retro-)directions (e.g., Contact Fault and Border Ranges Fault in the Yakutat collision zone of southeast Alaska; Arkle et al, 2013) are characteristic features of many continental orogens described as "doubly vergent" (Argand, 1916;Eizenhöfer et al, 2021;Willett et al, 1993).…”
Section: Discussionmentioning
confidence: 99%